2004
DOI: 10.1021/ja044517c
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Assessment of the Influence of Permanent Kinks on the Mixing Behavior of Phospholipids in Cholesterol-Rich Bilayers

Abstract: The mixing behavior of a phospholipid containing a cis-cyclopropyl moiety (1) with one that contains two myristoyl groups (3a) has been investigated in fluid bilayers via the nearest-neighbor recognition (NNR) method. In the absence of cholesterol, these lipids mix ideally. In the presence of cholesterol, they show a modest preference for homo-phospholipid association. A trans-form of 1 (i.e., 2) was found to have similar behavior, except that the influence of cholesterol in promoting homo-phospholipid associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 22 publications
1
18
1
Order By: Relevance
“…Peaks at -0.30 ppm, 0.60 ppm, and 0.68 ppm were observed, agreeing with some literature data (3,8,12), and correlated with 13 bons. In other reports (3,7,(11)(12), the two peaks observed in the present work at 0.60 and 0.68 ppm apparently were not resolved. In the present work, 2D homonuclear correlation showed that the peaks at -0.30 and 0.60 ppm are assigned to the two C3 protons of the cyclopropane ring-cis and trans, respectively-and that the two methine protons resonate slightly downfield at 0.68 ppm.…”
Section: Resultscontrasting
confidence: 87%
See 2 more Smart Citations
“…Peaks at -0.30 ppm, 0.60 ppm, and 0.68 ppm were observed, agreeing with some literature data (3,8,12), and correlated with 13 bons. In other reports (3,7,(11)(12), the two peaks observed in the present work at 0.60 and 0.68 ppm apparently were not resolved. In the present work, 2D homonuclear correlation showed that the peaks at -0.30 and 0.60 ppm are assigned to the two C3 protons of the cyclopropane ring-cis and trans, respectively-and that the two methine protons resonate slightly downfield at 0.68 ppm.…”
Section: Resultscontrasting
confidence: 87%
“…Two-dimensional homonuclear correlation shows clear correlation with the triplet caused by the protons attached to C2, indicating that this signal is assigned to the C3 methylene protons. On the other hand, the peak at 1.17 ppm, which was not resolved or listed separately in the previous literature, with one exception (11), correlates with the signal of the methine protons at 0.68 ppm and is therefore assigned to methylene protons · to the cyclopropane ring. However, the peak at 1.17 ppm is caused by two protons.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…2730 Monolayer measurements that were made at the air/water interface, and also differential scanning calorimetry measurements that were made of bilayers, have shown that a cyclopropyl group is, in fact, an excellent surrogate for a cis-double bond. 31 Based on the use of these kinked and exchangeable phospholipids, we found that each of these phospholipids exhibited repulsive interactions with 3, such that the strength of this repulsion increased, steadily as the number of permanent kinks increased; i.e., where the ω AB value increased from +160 « 30 to +250 « 45 to +430 « 51 cal/mol on going from 4 to 5 to 6. It is also noteworthy that the magnitude of the repulsive interaction between 3 and 4 is essentially the same as that reported for the interaction between cholesterol and POPC.…”
Section: Exchangeable Lipid Mimicsmentioning
confidence: 91%
“…3,4 These significant biological functions and pharmaceutical applications of the natural phospholipids have incited researchers to develop several unnatural lipids to improve properties of lipids and diversify its applications. [1][2][3][5][6][7] Surprisingly, all the efforts have been concentrated on modifying the headgroups, hydrophobic tails and the linker region between the headgroup and the tails of the lipid, without altering the phosphate moiety. Recently reported inversephosphatidylcholine with inverted charge orientation in the choline headgroup leads to a number of interesting and complimentary properties in lipids.…”
Section: Phosphate Bioisostere Containing Amphiphiles: a Novel Class mentioning
confidence: 99%